Evaluation of corneal biomechanical properties in spherical and toric soft contact lens wear - Neeta Mishra; Mamta Tandale; Veshal Madan; Rekha Chotaliya; Uday Bajare (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2022)
Purpose: Corneal hysteresis (CH) and corneal resistance factor was found to be less for patient wearing toric contact lens as compared to soft spherical CH was calculated as the difference in air pressures between force-in applanation (P1) and force-out applanation (P2), or (P1–P2). Materials and Methods: This was the prospective study, 40 eyes of 22 patients with mean age of 22.09 ± 4.05 years. Eleven eyes were fitted with soft toric contact lens and 29 eyes were fitted with soft spherical contact lens. Dry eye, keratoconic or any systemic pathology were excluded. Soft toric and soft spherical contact lenses (Comfilcon A, Coopervision, and Southampton, UK) were fitted. The Ocular response Analyzer (Reichert Ophthalmic Instruments, Depew, New York, USA) was used to measure CH before and after 3 months using soft toric and soft spherical contact lenses. Descriptive statistics were used to analyze the demographic data. Paired t-test was employed for analyzing the difference between the base line value of CH with soft toric and soft spherical contact lens wearers after 3 months. Independent t-test was used to find the association between CH and gender. Results: CH was found to be lesser after 3 months of soft toric contact lens wear, as compared with soft spherical contact lenses. Mean increase of CH was found to range from 10.44 ± 0.96to 10.80 ± 0.96 mmHg (P = 0.000). Conclusion: In this study, there was a decrease in CH after using soft toric contact lenses and increase after using soft spherical contact lenses for 3 months. The increased CH with soft spherical contact lens was reversible in nature. However, CH may differ between lens type and modality of wear which can lead to long-term changes in the corneal biomechanical properties.